Policy on Assessing the Resilience of Territorial Command Personnel Capacity in Multi-Threat Disaster Mitigation in Cianjur Regency - Kristian, Indra; Herlia, Tati; Agus Kartomo (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
This research aims to provide an overview of the phenomena and opportunities for Disaster Mitigation by the Regional Command apparatus in Cianjur Regency, to further formulate an assessment model through the formulation of policies, strategies and effective disaster management steps. Data was collected through filling out questionnaires and interviews using polyphonic interviewing and oral analysis techniques, involving various relevant stakeholders. The data obtained was then analyzed through stages of reduction, classification and coding, resulting in in-depth conceptualization and thematization. The research results show that the capacity resilience of Apkowil Kodim 0608/Cianjur is in an intermediate position, which means that further strengthening is still needed in the fields of human resources and software, such as supporting regulations. This strengthening is very important to ensure effective preparedness and response to disasters. Thus, it is hoped that through this capacity increase, Apkowil can achieve the level of resilience that meets expectations, and be able to make a significant contribution in realizing a safe and resilient area against disasters.